Solar UV Irradiance Measurements at Four Sites in Tibet - Gelsor, Norsang; Pingcuo, Nima; Wangmu, Tsoja; Kjeldstad, Berit; Chen, Yi-Chun; Frett, Øyvind; Stamnes, Jakob J; Bhattarai, Binod K; Dhalback, Arne (Journal of the Institute of Engineering, 2012)
We present solar ultraviolet (UV) irradiance measurements at four sites in Tibet (Lhasa, Linzhi, Nagqu, and Tingri) for the period between July 2008 and September 2010. Erythemal UV dose rates and irradiances of solar UVA, UVB for all four sites are presented. Days with clear sky cloud transmittance (CLT) larger than 100% are particularly selected and analyzed for the four sites. Comparisons between the four sites are also carried out, and the clear-sky data analyses for the summer time show that Tingri (near Mt. Everest) has the highest UV irradiance, Lhasa the second highest, while Nagchu (Northen Tibet) and Linzhi (Eastern Tibet) have a bit lower values. Tingri has the strongest UV level among the four sites around the year, mainly due to increased albedo caused by snow-covered surroundings. UV data for Lhasa for the period from 2004 to 2010 are also analyzed, showing that the UV instantaneous irradiance trend for the recent six-year period is stable. However, the number of clear-sky days in Lhasa has increased over the recent six years, causing an increase in the yearly-integrated total UV irradiance. DOI: http://dx.doi.org/10.3126/jie.v8i3.5934 JIE 2011; 8(3): 75-86